A quantitative meta-analysis of vitamin C in the pathophysiology of Alzheimer’s disease - Hamid, Maryam; Mansoor, Sumaiya; Amber, Sanila; Zahid, Saadia (Frontiers in Aging Neuroscience, 2022)
Purpose Alzheimer’s disease (AD) is a multifaceted neurodegenerative disorder with many complex pathways feeding into its pathogenesis and progression. Vitamin C, an essential dietary antioxidant is vital for proper neurological development and maintenance. This meta-analysis and systematic review attempted to define the relationship between vitamin C plasma levels and AD while highlighting the importance and involvement of vitamin C in pathogenesis of AD. Methods PRISMA guidelines were used to obtain studies quantifying the plasma levels of vitamin C in AD and control subjects. The literature was searched in the online databases PubMed, Google scholar and Web of Science. A total of 12 studies were included (n=1100) and analyzed using comprehensive meta-analysis 3.0. Results The results show that there is a significant decrease in the plasma vitamin C levels of AD patients as compared to healthy controls (pooled SMD with random effect model: -1.164, with 95% CI: -1.720 to -0.608, Z = -4.102, p = 0.00) with significant heterogeneity (I2=93.218). The sensitivity analysis showed directionally similar results. Eggers regression test (p = 0.11) and visual inspection of the funnel plot showed no publication bias. Conclusion Based on these studies it can be deduced that the deficiency of vitamin C is involved in disease progression and supplementation is a plausible preventive and treatment strategy. However, clinical studies are warranted to elucidate its exact mechanistic role in AD pathophysiology and prevention. Keywords: Vitamin C, Alzheimer’s disease, Ascorbic acid, Amyloid beta, Oxidative stress